2009
DOI: 10.3346/jkms.2009.24.s1.s11
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Chronic Kidney Disease (CKD) and the Associated Factors to CKD in Urban Korea: A Population-based Cross-sectional Epidemiologic Study

Abstract: Chronic kidney disease (CKD) is a worldwide problem. This study was designed to survey the prevalence and risk factors for CKD in Korea. The 2,356 subjects were selected in proportion to age, gender, and city. Subjects 35 yr of age or older were selected from 7 cities. Estimated glomerular filtration rate (eGFR) was calculated using the Modification of Diet in Renal Disease (MDRD) Study equation, with albuminuria defined as a urine albumin to creatinine ratio of 30 mg/g or more. The overall prevalence of CKD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
102
4
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 30 publications
9
102
4
2
Order By: Relevance
“…Almost one half of them had at least one of the three markers: 25% had only MAU and/or proteinuria but not diminished eGFR, while 21% had eGFR below 60 mL/min/1.73 m 2 -14% without MAU and proteinuria and 7% with MAU and/or proteinuria. These results cannot be compared with those obtained in several massive screenings carried out in the general population where the prevalence of GFR below 60 mL/min/1.73 m 2 was between 3.2 and 11.2% 2,11,17,26,27 and albuminuria between 2.4 and 15.6%. 2,11,[26][27][28][29] The almost twice as high prevalence of CKD markers found here, where three groups of patients at increased risk of CKD were involved, is comparable to values determined in studies that also targeted different at-risk populations.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Almost one half of them had at least one of the three markers: 25% had only MAU and/or proteinuria but not diminished eGFR, while 21% had eGFR below 60 mL/min/1.73 m 2 -14% without MAU and proteinuria and 7% with MAU and/or proteinuria. These results cannot be compared with those obtained in several massive screenings carried out in the general population where the prevalence of GFR below 60 mL/min/1.73 m 2 was between 3.2 and 11.2% 2,11,17,26,27 and albuminuria between 2.4 and 15.6%. 2,11,[26][27][28][29] The almost twice as high prevalence of CKD markers found here, where three groups of patients at increased risk of CKD were involved, is comparable to values determined in studies that also targeted different at-risk populations.…”
Section: Discussioncontrasting
confidence: 38%
“…These results cannot be compared with those obtained in several massive screenings carried out in the general population where the prevalence of GFR below 60 mL/min/1.73 m 2 was between 3.2 and 11.2% 2,11,17,26,27 and albuminuria between 2.4 and 15.6%. 2,11,[26][27][28][29] The almost twice as high prevalence of CKD markers found here, where three groups of patients at increased risk of CKD were involved, is comparable to values determined in studies that also targeted different at-risk populations. The initial data of the well-known kidney early evaluation program (KEEP) that targeted persons with diabetes, hypertension, or a family history of diabetes or hypertension or CKD showed that, among 6071 participants, 29% had albuminuria and 16% had eGFR below 60 mL/min/1.73 m 2 .…”
Section: Discussioncontrasting
confidence: 38%
“…[21][22][23][24] The observed prevalence of CKD in our cirrhotic patients was 15.6%. The higher incidence of CKD in our study (15.6%) may be due to common denominator causing cirrhosis of liver and CKD, for example, viral infection (hepatitis B and C) is known to cause both.…”
Section: Discussionmentioning
confidence: 97%
“…and has increased remarkably recent years. The study established that the obesity may be the independent risk factor for development of CKD also in South Korea as the study indicated that higher BMIs were related to higher CKD prevalence (P<0.05) [26]. Over the past years, with the steady increase in rates, obesity emerges as major health threat in South Korea.…”
Section: Discussionmentioning
confidence: 99%